Obstetric Referral System during COVID-19 Pandemic : Tertiary Referral Hospital Perspective: istem Rujukan Obstetri dalam Masa Pandemi COVID-19 : Perspektif Rumah Sakit Rujukan Tersier - Arietta R. D. Pusponegoro; Chakti A. Swastika; Junita Indarti (Indonesian Socety of Obstetrics and Gynecology, 2022)
Abstract Objective : To evaluate the effectiveness of obstetric referrals to the dr. Cipto Mangunkusumo National Central General Hospital (RSCM), a tertiary hospital in Indonesian referral system, during the COVID-19 pandemic. Methods : A cross-sectional descriptive-analytic study that compared the effectiveness of referrals before (July-December 2019) and during the COVID-19 pandemic (March-August 2020) at the National Central General Hospital dr. Cipto Mangunkusumo (RSCM). Referral effectiveness is assessed based on two criteria, namely the suitability of the diagnosis and procedural compliance which includes communication through the integrated emergency response system (SPGDT), delivery by ambulance, and attachment of a referral letter. Results: The study found 198 referral cases from 464 obstetric cases (42.67%) before the pandemic and 231 referral cases from 486 obstetric cases (47.53%) during the pandemic. The diagnostic concordance increased from 57.58% before the pandemic to 71.00% during the pandemic (p = 0.004). Referral procedural compliance increased from 28.28% before the pandemic to 45.45% during the pandemic (p < 0.001). Based on these criteria, the effectiveness of referrals at the RSCM during the COVID-19 pandemic era was found to be significantly higher, namely before the pandemic by 21.72% and during the pandemic by 40.26% (p < 0.001). Conclusion : The effectiveness of referral to the RSCM based on the suitability of the diagnosis and the accuracy of the procedure during the COVID-19 pandemic was found to be better than before the pandemic. Keywords: COVID-19, obstetric referral system, pandemic. Abstrak Tujuan : Untuk menilai efektivitas rujukan obstetri ke Rumah Sakit Pusat Nasional dr. Cipto Mangunkusumo, rumah sakit tersier dalam sistem rujukan Indonesia, selama pandemi COVID-19 Metode: Penelitian deskriptif-analitik berdesain potong lintang yang membandingkan efektivitas rujukan sebelum (Juli-Desember 2019) dan saat pandemi COVID-19 (Maret-Agustus 2020) di Rumah Sakit Umum Pusat Nasional dr. Cipto Mangunkusumo (RSCM). Efektivitas rujukan dinilai berdasarkan dua kriteria, yakni kesesuaian diagnosis dan kepatuhan prosedur yang meliputi komunikasi melalui sistem penanggulangan gawat darurat terpadu (SPGDT), pengantaran dengan ambulans, dan pelampiran surat rujukan. Hasil: Penelitian menemukan 198 kasus rujukan dari 464 kasus obstetri (42,67%) sebelum pandemi dan 231 kasus rujukan dari 486 kasus obstetri (47,53%) saat pandemi. Kesesuaian diagnosis meningkat dari 57,58% sebelum pandemi menjadi 71,00% saat pandemi (p = 0,004). Kepatuhan prosedur rujukan meningkat dari 28,28% sebelum pandemi menjadi 45,45% saat pandemi (p < 0,001). Berdasarkan kriteria tersebut, efektivitas rujukan di RSCM pada era pandemi COVID-19 ditemukan lebih tinggi secara signifikan, yakni sebelum pandemi sebesar 21,72% dan saat pandemi sebesar 40,26% (p < 0,001). Kesimpulan: Efektivitas rujukan ke RSCM berdasarkan kesesuaian diagnosis dan kepatuhan prosedur saat pandemi COVID-19 ditemukan lebih baik. Kata kunci: COVID-19, pandemi, sistem rujukan obstetri